Effects of Fly Ash and Chemical Admixtures on the Rheological Properties of High-Concentration Full-Tailing Filling Slurry - Fulin Wang; Faguang Yang; Zhengping Yuan; Shijiao Yang (Advances in Civil Engineering)
Good fluidity is the precondition to ensure the pipeline transportation of the filling slurry. The admixture in the filling slurry will affect the rheological properties of the slurry. In this paper, yield stress (YS), viscosity coefficient (VC), and expansion (ED) of the filling slurry were measured by the MCR52 rheometer and expansion tester, respectively, and the influence regularities of the three kinds of admixtures including fly ash (FA), polycarboxylate superplasticizer (PS), and polyethylene oxide (PEO) on the rheological properties of the filling slurry were obtained. The results show that when other conditions are fixed, the fluidity of the slurry becomes worse with the increase of the amount of fly ash but improves with the increase of the amount of the polycarboxylate superplasticizer; polyethylene oxide is not suitable for the improvement of the fluidity of the high-concentration full-tailing filling slurry, and the fluidity of the slurry becomes worse rapidly with the increase of the amount of polyethylene oxide.